Problems of rural development - Winfried Urff; Heinz Ahrens (Intereconomics, 1976)
Bangladesh is handicapped by very unfavourable natural conditions, inter alia extreme floods and droughts, an unfavourable pattern of farm sizes and the consequences of rising oil prices. For these reasons agricultural production lagged behind the planned targets in the first two years of the First Five Year Plan (1973–78). In the third year of the Plan the situation seems to have somewhat changed for the better. If this is not only due to accidental factors like favourable weather conditions but also a consequence of the present Government's serious efforts, there may be a glimmer of hope for the country.
Keywords: 330; Bangladesh